The effect of chronic usage of Renin-Angiotensin-Aldosterone System Blocking Agents on Incidence of Contrast-Induced Nephropathy in patients with Diabetes Mellitus and Renal Insufficiency. A Restropesctive Cohort Study - astika widy utomo; dwi aris agung nugrahaningsih; iwan dwiprahasto (Jurnal Kardiologi Indonesia, 2019)
Background: This study was to investigate the effect of long term use of Renin-Angiotensin-Aldosterone System(RAAS) blocking agents on the incidence of Contrast-Induced Nephropathy(CIN) on patients with Diabetes Mellitus(DM) and renal insufficiency underwent Percutaneous Coronary Intervention (PCI). Methods:A total 281 of subjects were included in this study and divided into two groups based on prior use of RAAS blocking agents (RAAS +, n = 146; RAAS -, n = 135). CIN was defined as an increase of ≥25% in creatinin over baseline value 48-72 hours after PCI. Result: Total incidence of CIN was 14,95%. There was no difference in the incidence of CIN between 2 study groups (p = 0,952) and relatif risk for CIN was 1,02. Left Ventricular ejection Fraction (LVEF) ≤ 40 % (OR 2,300; 95% CI 1,028 – 5,143; p = 0,043), anemia (OR 2,628; 95% CI 1,274 – 5,422; p = 0,009) and Glomerular Filtration rate (GFR) pre PCI ≤ 60 mL/menit (OR 2,782; 95% CI 1,293 – 5,987; p = 0,009) were important predictors of CIN. Conclusion: Long term use of RAAS blocking agents do not increase the incidence of CIN on patients with DM and renal insufficiency underwent PCI.